The Representation of Ternate Oral Literature in The Perspective of Literary Ecology - Samsudin Hi Adam; Silvani Umar Ali (Departement of Mathematics Education, 2023)
Nowadays, ecology has developed rapidly since it is no longer limited to the study of ecosystems or nature, but also used to study other fields including in literary studies. Many scholars argue that literature is closely related and inseparable to ecology. The large number of literary works containing nature and the environment shows that the writers have cared for nature from a long time ago. The study aims to analyze the representation of Ternate oral literature in the perspective of literary ecology. This study apllies descriptive qualitative method. Technique data collection used is documentation technique. Sources of data for this study were obtained from various sources of Ternate oral literature documents found in libraries and other relevant sources. In addition, the researchers used browsing’ techniques to find relevant data. Triangulation techniques are still used to check valid data from various sources. The result shows that the representation of Ternate oral literature viwed from ecological perspective is shown in the form of fables and poetry (dola bololo, dalil moro, and dalil tifa) which implie moral and ethical values to become lessons for the community and readers of literature. In addition, the implied message from fables and poetry in Ternate oral literature is that living things and their natural environment play a role in life and also influence the thinking of the people of Ternate which of course must be maintained and preserved because they are useful for the community itself.